Fear and agony of the pandemic leading to stress and mental illness: An emerging crisis in the novel coronavirus (COVID-19) outbreak - Fofana, Nina Kadidiatou; Latif, Faiza; Sarfraz, Summaira; Bilal; Bashir, Muhammad Farhan; Komal, Bushra (Psychiatry research, 2020)
The outbreak of novel Coronavirus (COVID-19), later named as a pandemic affecting nearly 210 countries and territories has led to negative emotions of fear and agony in the general population and healthcare staff professionals. The healthcare regulators and the governments have imposed emergencies and lockdowns in their countries which has led to an adverse effect on the mental health of people ultimately leading to a rise in anxiety, depression, and associated mental illness. The fear and uncertainty increased by the COVID-19 crisis are putting extreme pressure on our finite resources. This report aims to synthesis the dilemma of mental illness as a result of pandemic and initiates suggestions to help the general public, healthcare professionals, and workers mitigate the negative emotions to improve the mental wellbeing in this detached period of isolation.